Science Education and Culture
XII, 376 p. 6 illus.
Keywords: This anthology contains selected papers from the 'Science as Culture' conference held at Lake Como, and Pavia University Italy, 15-19 September 1999. The conference, attended by about 220 individuals from thirty countries, was a joint venture of the International History, Philosophy and Science Teaching Group (its fifth conference) and the History of Physics and Physics Teaching Division of the European Physical Society (its eighth conference). The magnificient Villa Olmo, on the lakeshore, provided a memorable location for the presentors of the 160 papers and the audience that discussed them. The conference was part of local celebrations of the bicentenary of Alessandro Volta's creation of the battery in 1799. Volta was born in Como in 1745, and for forty years from 1778 he was professor of experimental physics at Pavia University. The conference was fortunate to have had the generous financial support of the Italian government's Volta Bicentenary Fund, Lombardy region, Pavia University, Italian Research Council, and Kluwer Academic Publishers. The papers included here, have or will be, published in the journal Science & Education, the inaugural volume (1992) of which was a landmark in the history of science education publication, because it was the first journal in the field devoted to contributions from historical, philosophical and sociological scholarship. Clearly these 'foundational' disciplines inform numerous theoretical, curricular and pedagogical debates in science education. Contemporary Concerns The reseach promoted by the International and European Groups, and by the journal, is central to science education programmes in most areas of the world.